The Start And Process Of The Sumgait Pogroms Of The Armenian Population - Sharafyan, Narek (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
There are a lot of testimonies, reports of international organisations, court evidence, investigative-judicial protocols as well as court verdicts on the massacres of the Armenian population in the city of Sumgait (Sumqayit) in the Soviet Socialist Republic of Azerbaijan, committed from February 27 to February 29 in 1988. The aforementioned documents and evidence allow us to comprehensively present the course of events. However, it should be highlighted that in political and, in some cases, scientific circles, these tragic events are sometimes viewed as mere hooliganism, a result of exclusively hooligan-motivated killings. Սումգայիթի հայ բնակչության զանգվածային սպանությունների (հայտնի են նաև որպես «Սումգայիթի պոգրոմ») մեկնարկի և ընթացքի հանգամանքների մասին փաստական տվյալների բազմակողմանի վերլուծությունը վկայում է այն մասին, որ ազգային ատելության շարժառիթով կատարված զանգվածային սպանությունները եղել են կազմակերպված և համակարգված։ Всесторонний анализ фактических данных об обстоятельствах начала и ходе массовых убийств армянского населения в Сумгаите (известных также как «Сумгаитский погром») свидетельствует о том, что массовые убийства, основанные на национальной ненависти, были организованы и скоординированы. Они были результатом дискриминационной политики в отношении армянского населения, проводимой в Азербайджане. Следует отметить, что в Сумгаитской бойне присутствовали элементы международных преступлений.
Keywords: History